Internalization of Character Education in History Learning Occupation of Japan and the Proclamation of Independence at SMK PGRI 1 Mejobo Kudus - Chasanah, Anisatul; Utomo, Cahyo Budi (Indonesian Journal of History Education, 2022)
This research aims to determine the role of history subjects in forming the character of students at SMK PGRI 1 Mejobo Kudus, understand the process of internalizing character values in history subjects at SMK PGRI 1 Mejobo Kudus, and determine the influence of internalization of character education on student learning outcomes on the material on the Japanese Occupation and the Proclamation of Independence of the Republic of Indonesia. This research approach is a mixed method with a concurrent embedded strategy. The samples in this study, classes XRPL, X AKL, and X TKKR 1 were taken using simple random and purposive sampling techniques. Data collection techniques use observation techniques, tests, student behavior measurement scales, interviews, and documentation. The research results show that history has a role in character formation by inserting character values into learning. Internalizing character education starts with preparing learning plans and ends with evaluating history learning. Simple linear regression obtained a significant value (Asymp. Sig 2-tailed) 0.2. The residual value is usually distributed normally because the significant value is greater than 0.05. This means there is a positive influence between the internalization of character education and learning outcomes. Of the 40 respondents, 72.5% of the students showed they had completed learning the material on the Japanese Occupation and the Proclamation of Indonesian Independence.